Negative electrode material metal pre-activation device and metal pre-activation method
By designing a metal pre-activation device including a reaction chamber and a dry chamber, the problem of complex processes and high costs in the prior art is solved, and a safe and efficient lithiation process is achieved, which is suitable for large-scale mass production, and the battery is improved. Overall performance and reliability.
Patent Information
- Application Number
- CN202411695213.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2044-11-25
AI Technical Summary
The existing metal pre-activation technology of the negative electrode material has problems such as complex process, high cost, high operational risk, and difficulty in achieving mass production, which limits its large-scale application.
A metal pre-activation device including a longitudinally arranged reaction chamber and a dry chamber is designed to achieve a safe and efficient lithiation process through pipelines, valves and processing systems, and precisely control temperature and humidity to improve reaction efficiency.
It improves operational safety and efficiency, reduces production costs, is suitable for large-scale mass production, enhances the overall performance and reliability of the battery, and improves product consistency and quality control.
Smart Images

Figure CN119495747A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium ion battery preparation, and in particular relates to a device for preactivating metal of negative electrode material and a method for preactivating metal. Background Art
[0002] With the continuous development of secondary battery technology, the modification and optimization of negative electrode materials have become the key to improving battery performance. In recent years, metal pre-activation of negative electrode materials has gradually attracted the attention of the industry as an emerging technology. Metal pre-activation refers to the introduction of active metal elements (such as lithium, sodium, etc.) on the surface or inside of the negative electrode material to supplement the loss of active metal elements caused by the side reaction between the electrode material and the electrolyte, thereby improving the first effect and cycle life of the secondary battery. For example, the negative electrode material of the lithium-ion battery faces the problem of irreversible loss of lithium ions during the first charging process. During the initial charging, the negative electrode reacts with the electrolyte to form a solid electrolyte interface (SEI) film. This process will cause irreversible loss of lithium ions, which will lead to a decrease in capacity and a decrease in the first coulombic efficiency. Therefore, in order to improve the initial efficiency and stability of the battery, pre-lithiation technology, as a kind of metal pre-activation technology, came into being. In lithium-ion batteries, the performance of the negative electrode material directly affects the energy density, cycle stability and safety of the battery. However, the negative electrode will react strongly with the electrolyte during the first charge to form a solid electrolyte interface (SEI) film, which leads to irreversible loss of lithium ions, irreversible capacity loss and low first coulombic efficiency. In order to solve this problem, pre-lithiation technology came into being.
[0003] Pre-lithiation refers to the introduction of additional lithium into the negative electrode material before the battery is assembled to compensate for the lithium loss during the initial charging process. This technology can not only improve the initial coulombic efficiency of the battery, but also improve the cycle stability and charge and discharge performance of the battery to a certain extent. However, existing pre-lithiation methods, such as physical pre-lithiation, chemical pre-lithiation, electrochemical pre-lithiation, etc., often have problems such as complex processes, high costs, high operational risks, and difficulty in mass production, which limits the large-scale application of pre-lithiation technology. The main principle of electrochemical pre-lithiation technology is to transfer lithium ions to the negative electrode material using a lithium source and an external current. The implementation of this method usually relies on the construction of a specific structure. Its advantage is that it can achieve a higher pre-lithiation efficiency, and at the same time it can better control the degree of pre-lithiation to avoid performance degradation caused by excessive lithiation. The existing electrochemical pre-lithiation technology, such as CN116722239A, directly immerses the electrode to be pre-lithiated and the counter electrode lithium source in a container filled with electrolyte, and applies current for pre-lithiation. This solution is difficult to process the electrode on a large scale and is only applicable to laboratory level; another example is CN116053607A and CN219321383U, which simultaneously install the integrated battery cell and the lithium source in the electrochemical pre-lithiation device, connect the positive and negative pole ears of the battery cell and the lithium source pole ears respectively, and after the liquid is injected, the battery cell is pre-lithiated by applying current. Pre-lithiation is carried out, and the battery cell is removed from the device after the reaction. Since the actual integrated battery cell is a multi-layer structure, this solution will have the problem of serious uneven pre-lithiation degree of different pole pieces; for example, CN114026712A pre-lithiates the negative electrode of the battery cell by adding a third electrode inside the battery pack to connect the lithium source, and then seals the soft pack to separate the third electrode to leave the pre-lithiated battery cell. This solution adds three electrodes for pre-lithiation to the unsealed soft pack battery, which is cumbersome to operate, and the amount that can be processed each time is very limited. In addition, the battery cell structure is changed, and there are safety hazards.
[0004] However, the existing negative electrode material metal preactivation methods have problems such as complex process, high cost, high operation risk, and difficulty in mass production, which limits the large-scale application of metal preactivation technology. In view of the shortcomings of the existing technology, it is still necessary to develop a new negative electrode material metal preactivation device to solve the problems existing in metal preactivation, especially pre-lithiation methods. Summary of the invention
[0005] The present invention aims to solve at least one of the above-mentioned technical problems existing in the prior art. To this end, the present invention provides a metal preactivation device for negative electrode materials, which improves the safety and efficiency of operation, reduces production costs, and does not require changes to existing battery cell production line equipment and process. The device is easy to scale up and is suitable for large-scale mass production.
[0006] The invention also provides a metal preactivation method for negative electrode materials.
[0007] The first aspect of the present invention provides a metal preactivation device for negative electrode materials, comprising a reaction chamber and a drying chamber arranged longitudinally, wherein a pipeline is connected between the reaction chamber and the drying chamber, a valve is arranged on the pipeline, an active metal electrode is arranged in the reaction chamber, a filter screen and a heating device are arranged in the drying chamber, and the drying chamber is also connected to an exhaust gas treatment system and a waste liquid treatment system.
[0008] A technical solution in the metal preactivation device for negative electrode materials of the present invention has at least the following beneficial effects:
[0009] Higher operational safety. The metal preactivation device of the present invention effectively avoids the leakage of harmful gases and environmental pollution that may occur during the lithiation process by providing a reaction chamber and a drying chamber, and connecting pipelines, valves and an exhaust gas treatment system between the two. The sealing of the reaction chamber and the exhaust gas treatment system can effectively collect and purify the gases (such as hydrogen or harmful gases) generated by the reaction, reducing the safety risks during operation. The design of the drying chamber and the waste liquid treatment system helps to effectively manage the waste liquid or by-products generated during the lithiation process to avoid their pollution to the environment, while also ensuring that the waste treatment during operation does not affect the overall production.
[0010] Higher operating efficiency and lower production costs. The metal preactivation device of the present invention can improve the efficiency of the metal preactivation reaction by accurately controlling the active metal electrodes in the reaction chamber and the temperature and humidity in the drying chamber. Accurate temperature and humidity control can accelerate the lithiation reaction, while avoiding unnecessary waste of time, reducing energy consumption, and thus effectively reducing production costs. The device adopts a batch processing method, which can perform metal preactivation treatment on negative electrode materials on a large scale, solving the bottleneck problem in traditional metal preactivation methods, improving production capacity, and meeting the needs of large-scale industrial production.
[0011] The overall performance and reliability of the battery are enhanced. Specifically, the metal preactivation device can be used to more finely control the negative electrode material, ensuring that the negative electrode material can obtain a uniform activation effect during the metal preactivation process. This helps to improve the structural stability and electrochemical properties of the negative electrode material and enhance the cycle life, capacity and efficiency of the battery. The heating device is used in combination with the drying chamber to control the temperature and humidity in the reaction environment and optimize the metal preactivation process. By reasonably adjusting these parameters, over-activation or incomplete activation of the negative electrode material can be effectively avoided, thereby ensuring the overall performance of the battery.
[0012] Improved product consistency and quality control. The metal preactivation device of the present invention has precise process control capabilities and can monitor the reaction, drying, filter processing and other steps to ensure that the operation of each link is carried out under optimal conditions. This automated precise control can effectively improve the quality consistency of the product, reduce the errors caused by human operation, and ensure the consistency of the performance of each batch of negative electrode materials. Through the optimized metal preactivation process, the unevenness and defects in the material can be reduced, the consistency and reliability of the material can be improved, thereby reducing the scrap rate in production and further reducing production costs.
[0013] Furthermore, the metal preactivation device of the present invention is provided with a tail gas treatment system and a waste liquid treatment system, which helps to remove harmful gases and waste liquids generated during the lithiation process, ensures environmental protection and complies with environmental protection laws and regulations. This is of great significance for reducing environmental pollution during the production process and avoiding the harm of harmful substances to workers and the surrounding environment.
[0014] Furthermore, the metal preactivation device of the present invention is flexible and scalable, and can adapt to the metal preactivation of different negative electrode materials. The device is designed to be able to adapt to a variety of different types of negative electrode materials for metal preactivation treatment, including materials in different forms (such as powders, sheets, etc.), which makes it have good versatility and flexibility in the lithium battery production process and meet diverse production needs. Through modular design, the device can flexibly increase or decrease each unit as needed, thereby meeting the different needs from small-scale test production to large-scale industrial production, and has good scalability.
[0015] Therefore, the present invention provides a novel electrochemical metal preactivation device for negative electrode materials of lithium-ion batteries. The device aims to improve the safety and efficiency of operation, reduce production costs, and enhance the overall performance and reliability of the battery by improving the metal preactivation process. It can directly perform large-scale metal preactivation treatment on negative electrode powder materials, and is compatible with subsequent battery production line equipment and process procedures without changing the existing battery production line equipment and process procedures. The device is easy to scale up and suitable for large-scale mass production.
[0016] According to some embodiments of the present invention, the active metal electrode includes an active material layer, a copper current collector layer and a separator layer arranged in sequence.
[0017] According to some embodiments of the present invention, the active metal electrode is a spirally coiled structure.
[0018] According to some embodiments of the present invention, the spiral curled structure may have multiple layers. If more materials need to be processed, the device may be made larger and have more layers.
[0019] According to some embodiments of the present invention, the reaction chamber includes a reaction chamber cylinder, and a reaction chamber upper cover and a reaction chamber lower cover detachably connected to the reaction chamber cylinder, and the reaction chamber cylinder, the reaction chamber upper cover and the reaction chamber lower cover are made of insulating material.
[0020] According to some embodiments of the present invention, the reaction chamber cylinder and the reaction chamber upper cover are connected by fastening bolts, and a sealing rubber ring is provided between the reaction chamber cylinder and the reaction chamber upper cover.
[0021] According to some embodiments of the present invention, the reaction chamber is provided with a first electrode and a second electrode connected to the active metal electrode, the reaction chamber cover is provided with a first through hole and a second through hole, and the first electrode and the second electrode are respectively inserted into the interior of the reaction chamber through the first through hole and the second through hole.
[0022] According to some embodiments of the present invention, the reaction chamber is further provided with a liquid injection port and a reaction chamber pressure gauge. The liquid injection port is used to inject electrolyte into the reaction chamber. The pressure gauge monitors the pressure in the chamber during the reaction.
[0023] According to some embodiments of the present invention, the injection port is connected to an injection pump.
[0024] According to some embodiments of the present invention, the interior of the reaction chamber is divided into a negative electrode powder containing area and an active metal electrode area.
[0025] According to some embodiments of the present invention, the drying bin includes a drying bin cylinder, and a drying bin upper cover and a drying bin lower cover detachably connected to the drying bin cylinder, and the drying bin cylinder, the drying bin upper cover and the drying bin lower cover are made of insulating material.
[0026] According to some embodiments of the present invention, the drying bin cylinder body and the drying bin upper cover are connected by fastening bolts, and a sealing rubber ring is provided between the drying bin cylinder body and the drying bin upper cover.
[0027] According to some embodiments of the present invention, the heating device is a heating coil.
[0028] According to some embodiments of the present invention, the drying chamber is further provided with a drying chamber pressure gauge, a liquid extraction pump interface, a vacuum pump interface and a thermometer.
[0029] According to some embodiments of the present invention, the liquid pump interface is connected to a liquid pump.
[0030] According to some embodiments of the present invention, the metal preactivation device is connected to an external power source, and the external power source is connected to the first electrode and the second electrode.
[0031] The second aspect of the present invention provides a method for preactivating metal of negative electrode material using the metal preactivation device of the first aspect of the present invention, comprising the following steps:
[0032] S1: adding the negative electrode material to be treated into the reaction chamber, injecting the electrolyte, and turning on the power supply to perform metal pre-activation treatment;
[0033] S2: Open the valve, the negative electrode material that has been pre-activated by metal enters the drying chamber from the reaction chamber, the waste liquid flows through the filter and is removed, and the heating device is turned on to dry the negative electrode material to obtain the negative electrode material that has been pre-activated by metal.
[0034] A technical solution in the method for preactivating metal of negative electrode material of the present invention has at least the following beneficial effects:
[0035] It can improve the cycle stability of negative electrode materials. Through metal pre-activation treatment, the negative electrode material can react with lithium before being put into battery assembly to form a stable solid electrolyte interface (SEI) film. The formation of the SEI film can significantly improve the cycle stability of the negative electrode material and reduce the side reactions caused by direct contact between the electrolyte and the negative electrode material during the charge and discharge process.
[0036] It can improve the initial capacity of the battery. The negative electrode material that has been pre-activated by metal (such as pre-lithiation) can reduce the consumption of active ions (such as lithium ions) during the initial charge, thereby increasing the initial capacity of the battery. Pre-activation helps to "activate" the negative electrode material in advance, ensuring a more efficient charging process.
[0037] Reduced waste of active metal sources. By first reacting the activated metal elements with the negative electrode material during the pre-activation process, the waste of active metal elements during the charging process after the battery is assembled is avoided, thereby improving the utilization efficiency of the active metal elements. The process of the method of the present invention includes the steps of pre-activation, waste liquid removal and drying treatment, which can effectively remove the residues in the electrolyte and ensure that the performance of the negative electrode material is not damaged during the drying process, thereby improving the production efficiency and material utilization.
[0038] Improved safety. By controlling the reaction between the electrolyte and the negative electrode material during the metal pre-activation process, possible safety hazards can be eliminated during the production stage, reducing overheating or other electrochemical instability in the subsequent use of the battery.
[0039] Improved consistency of negative electrode materials. The method of the present invention ensures that each batch of negative electrode materials can be uniformly processed by standardizing the metal pre-activation process, thereby improving the quality consistency of the negative electrode materials and ensuring the consistency and reliability of the battery.
[0040] Reduced complexity of post-processing. Since the metal pre-activation treatment can effectively remove excess electrolyte and impurities, and further process them in the subsequent drying process, it simplifies the subsequent material processing steps and improves the simplicity and controllability of the entire manufacturing process.
[0041] Therefore, the metal preactivation method of the present invention can improve battery performance while reducing production costs, improving the efficiency and safety of the manufacturing process, and has significant industrial application value.
[0042] According to some embodiments of the present invention, the electrolyte salt in the electrolyte includes at least one of lithium salt, sodium salt, potassium salt, calcium salt, and magnesium salt, such as lithium hexafluorophosphate, lithium bis(trifluoromethanesulfonyl imide), lithium tetrafluoroborate, lithium trifluoromethanesulfonate, lithium difluorooxalatoborate, and lithium nitrate.
[0043] According to some embodiments of the present invention, the solvent added to the electrolyte is at least one of ethylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, dioxolane, and ethylene glycol dimethyl ether.
[0044] According to some embodiments of the present invention, the electrolyte solvent additive is at least one of vinylene carbonate, fluoroethylene carbonate, vinyl sulfate, and propylene sulfite.
[0045] Connect the first electrode column and the second electrode column to the designated electrode. The current and time are determined according to the nominal specific capacity, first-week coulomb and efficiency of the negative electrode material. Turn on the power supply to perform metal preactivation. After the metal preactivation is completed, open the valve and the vacuum pump connected to the liquid extraction port to allow the mixture to enter the drying chamber.
[0046] After the metal pre-activated negative electrode material powder is loaded into the drying chamber, the valve is closed, and the filter screen will filter the material. Then, the vacuum pump interface is connected and started to extract the filtered waste liquid, and the heating coil is started to adjust the temperature of the reaction chamber. The pressure of the drying chamber is adjusted by an external vacuum pump through the vacuum pump interface. The pressure gauge and thermometer display and feedback, and the liquid and gas extracted by the vacuum pump are treated as waste liquid and exhaust gas.
[0047] According to some embodiments of the present invention, the drying process is carried out at a temperature of 70°C to 90°C.
[0048] According to some embodiments of the present invention, the drying process is carried out at a temperature of 80°C.
[0049] According to some embodiments of the present invention, the drying process is performed for 8 to 10 hours.
[0050] According to some embodiments of the present invention, during the drying process, the pressure of the drying chamber is 1×10 - 4Pa~1×10 -2 Pa.
[0051] According to some embodiments of the present invention, during the drying process, the pressure of the drying chamber is 1×10 - 3 Pa.
[0052] According to some embodiments of the present invention, a method for preactivating a negative electrode material metal using the metal preactivation device of the first aspect of the present invention comprises the following steps:
[0053] S1: Open the upper cover of the reaction chamber, add the raw material negative electrode material powder into the reaction chamber, close the upper cover of the reaction chamber and seal it, open the injection port to inject the electrolyte, connect the first electrode column and the second electrode column to the positive and negative electrodes of the power supply respectively, and after sufficient reaction, obtain a mixture of the metal pre-activated negative electrode and the electrolyte;
[0054] S2: Open the valve of the reaction chamber and the vacuum pump connected to the liquid extraction port of the drying chamber to allow the mixture to enter the drying chamber. After the mixture enters the drying chamber, the lower layer of liquid is extracted through the external liquid extraction pump of the liquid extraction port to accelerate the filtration of the material by the filter. After the filtration is completed, the valve is closed, and the power supply of the heating coil is turned on to heat the mixture. Then, the pressure of the drying chamber is reduced through the vacuum pump interface. The temperature and pressure in the chamber are fed back in real time by the pressure gauge and thermometer. The extracted liquid needs to be treated as waste liquid, and the gas extracted by the vacuum pump needs to be treated as tail gas. After drying, open the drying chamber cover of the drying chamber to take out the finished product, which is the finished metal pre-activated negative electrode material powder.
[0055] The device and method of the present invention are applicable to other secondary battery negative electrode materials besides lithium ion batteries, including sodium ion batteries, potassium ion batteries, calcium ion batteries, magnesium ion batteries, and mixed ion batteries, such as lithium-sodium mixed ion batteries, lithium-potassium mixed ion batteries, lithium-calcium mixed ion batteries, lithium-magnesium mixed ion batteries, sodium-potassium mixed ion batteries, sodium-calcium mixed ion batteries, sodium-magnesium mixed ion batteries, calcium-magnesium mixed ion batteries, etc.
[0056] The third aspect of the present invention provides a secondary battery negative electrode material obtained by pre-activation using the device of the first aspect or the method of the second aspect of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0057] Figure 1 It is a schematic diagram of the structure of a metal preactivation device.
[0058] Figure 2 It is a schematic diagram of the structure of the reaction chamber and the drying chamber.
[0059] Figure 3 It is a schematic diagram of the structure of active metal electrode.
[0060] Figure 4 is a top view of the active metal electrode.
[0061] Figure 5 It is a schematic diagram of the reaction chamber structure.
[0062] Figure 6 This is the energy spectrum test result of the negative electrode material prepared in Example 1.
[0063] Figure 7 This is the X-ray powder diffraction test result of the negative electrode material prepared in Example 1.
[0064] Figure 8 This is the first cycle charge and discharge curve of the original graphite in Example 1.
[0065] Fig. 9 This is the first cycle charge and discharge curve of the metal pre-activated graphite in Example 1.
[0066] Reference numerals:
[0067] Reaction chamber 1000, active metal electrode 1001, lithium material layer 1002, copper current collector layer 1003, diaphragm layer 1004, reaction chamber cylinder 1005, reaction chamber upper cover 1006, reaction chamber lower cover 1007, fastening bolts 1008, sealing rubber ring 1009, first electrode 1010, second electrode 1011, liquid injection port 1012, negative electrode powder storage area 1013;
[0068] Drying bin 2000, filter screen 2001, heating device 2002, drying bin cylinder 2003, drying bin upper cover 2004, drying bin lower cover 2005, liquid pump interface 2006, vacuum pump interface 2007, drying bin pressure gauge 2008, thermometer 2009;
[0069] Pipeline 3000, valve 3001. DETAILED DESCRIPTION
[0070] The following are specific embodiments of the present invention, and the technical solutions of the present invention are further described in conjunction with the embodiments, but the present invention is not limited to these embodiments.
[0071] In a first aspect, some embodiments of the present invention provide a metal preactivation device for a negative electrode material, referring to Figure 1 As shown, it includes a reaction chamber 1000 and a drying chamber 2000 arranged vertically (i.e., arranged up and down), a pipeline 3000 is connected between the reaction chamber 1000 and the drying chamber 2000, and a valve 3001 is arranged on the pipeline. Figure 2As shown, an active metal electrode 1001 is disposed in the reaction chamber 1000, a filter screen 2001 and a heating device 2002 are disposed in the drying chamber 2000, and the drying chamber 2000 is also connected to an exhaust gas treatment system and a waste liquid treatment system.
[0072] It can be understood that the metal preactivation device of the negative electrode material of the present invention has at least the following beneficial effects:
[0073] Higher operational safety. The metal preactivation device of the present invention effectively avoids the leakage of harmful gases and environmental pollution that may occur during the lithiation process by providing a reaction chamber and a drying chamber, and connecting pipelines, valves and an exhaust gas treatment system between the two. The sealing of the reaction chamber and the exhaust gas treatment system can effectively collect and purify the gases (such as hydrogen or harmful gases) generated by the reaction, reducing the safety risks during operation. The design of the drying chamber and the waste liquid treatment system helps to effectively manage the waste liquid or by-products generated during the lithiation process to avoid their pollution to the environment, while also ensuring that the waste treatment during operation does not affect the overall production.
[0074] Higher operating efficiency and lower production costs. The metal preactivation device of the present invention can improve the efficiency of the metal preactivation reaction by accurately controlling the active metal electrodes in the reaction chamber and the temperature and humidity in the drying chamber. Accurate temperature and humidity control can accelerate the lithiation reaction, while avoiding unnecessary waste of time, reducing energy consumption, and thus effectively reducing production costs. The device adopts a batch processing method, which can perform metal preactivation treatment on negative electrode materials on a large scale, solving the bottleneck problem in traditional metal preactivation methods, improving production capacity, and meeting the needs of large-scale industrial production.
[0075] The overall performance and reliability of the battery are enhanced. Specifically, the metal preactivation device can be used to more finely control the negative electrode material, ensuring that the negative electrode material can obtain a uniform lithiation effect during the metal preactivation process. This helps to improve the structural stability and electrochemical properties of the negative electrode material and enhance the cycle life, capacity and efficiency of the battery. The heating device is used in combination with the drying chamber to control the temperature and humidity in the reaction environment and optimize the metal preactivation process. By reasonably adjusting these parameters, excessive lithiation or incomplete lithiation of the negative electrode material can be effectively avoided, thereby ensuring the overall performance of the battery.
[0076] Improved product consistency and quality control. The metal preactivation device of the present invention has precise process control capabilities and can monitor the reaction, drying, filter processing and other steps to ensure that the operation of each link is carried out under optimal conditions. This automated precise control can effectively improve the quality consistency of the product, reduce the errors caused by human operation, and ensure the consistency of the performance of each batch of negative electrode materials. Through the optimized metal preactivation process, the unevenness and defects in the material can be reduced, the consistency and reliability of the material can be improved, thereby reducing the scrap rate in production and further reducing production costs.
[0077] Furthermore, the metal preactivation device of the present invention is provided with a tail gas treatment system and a waste liquid treatment system, which helps to remove harmful gases and waste liquids generated during the lithiation process, ensures environmental protection and complies with environmental protection laws and regulations. This is of great significance for reducing environmental pollution during the production process and avoiding the harm of harmful substances to workers and the surrounding environment.
[0078] Furthermore, the metal preactivation device of the present invention is flexible and scalable, and can adapt to the metal preactivation of different negative electrode materials. The device is designed to be able to adapt to a variety of different types of negative electrode materials for metal preactivation treatment, including materials in different forms (such as powders, sheets, etc.), which makes it have good versatility and flexibility in the lithium battery production process and meet diverse production needs. Through modular design, the device can flexibly increase or decrease each unit as needed, thereby meeting the different needs from small-scale test production to large-scale industrial production, and has good scalability.
[0079] Therefore, the present invention provides a novel electrochemical metal preactivation device for negative electrode materials of secondary batteries. The device aims to improve the safety and efficiency of operation, reduce production costs, and enhance the overall performance and reliability of the battery through precise control by improving the metal preactivation process. It can directly perform large-scale metal preactivation treatment on negative electrode powder materials, and is compatible with subsequent battery production line equipment and process procedures without changing the existing battery production line equipment and process procedures. The device is easy to scale up and suitable for large-scale mass production.
[0080] In conjunction with the first aspect, in some pre-lithiation embodiments of the present invention, reference is made to Figure 3 As shown, the active metal electrode 1001 includes a lithium material layer 1002, a copper current collector layer 1003 and a diaphragm layer 1004. The specific structure is that the copper current collector layer 1003, the lithium material layer 1002, the diaphragm layer 1004, the lithium material layer 1002 and the copper current collector layer 1003 are arranged in sequence.
[0081] In combination with the first aspect, in some embodiments of the present invention, reference Figure 3 and Figure 4As shown, the active metal electrode 1001 is a spirally curled structure. The spirally curled structure can increase the contact area between the lithium source and the metal pre-activated material. The diaphragm material used in the spiral electrode can be one of glass fiber, polypropylene (PP), polyethylene (PE), etc. The material and thickness are changed according to the material used and the electrolyte composition.
[0082] In the metal pre-activation device of the present invention, such as the pre-lithiation device, the structure of the active metal electrode includes a lithium material layer, a copper current collector layer and a separator layer. These three layers play different roles in the lithiation reaction, as follows:
[0083] The lithium material layer is the core part of the active metal electrode and provides a lithium-conducting medium. During the pre-lithiation process, the lithium in the lithium material layer migrates to the negative electrode material through chemical reactions to complete the lithiation reaction. The selection and design of the lithium material layer are crucial to ensure the release efficiency and stability of the lithium source and the smooth progress of the lithiation process. The lithium material layer is usually made of high-purity lithium metal or lithium-containing materials (such as lithium-based alloys, lithium-based composite materials, etc.), which can provide sufficient lithium ions in the pre-lithiation reaction.
[0084] The main function of the copper current collector layer is to provide a good conductivity path to conduct the current from the lithium material layer to the external circuit. In the negative electrode of a lithium-ion battery, the current collector layer is usually responsible for conducting the current from the electrode material to the external circuit of the battery, thereby ensuring the effective flow of current. Copper is a metal with excellent electrical conductivity, which can effectively transmit current and has good mechanical strength and corrosion resistance, making it suitable for use in the electrochemical reaction of lithium batteries.
[0085] The main function of the diaphragm layer is to prevent direct contact between the lithium material layer and the copper current collector layer, thereby avoiding safety problems such as short circuits. At the same time, the diaphragm layer can also ensure that lithium ions can pass effectively during the pre-lithiation process, promoting the lithiation reaction. The diaphragm layer is generally made of porous materials (such as polyethylene or polypropylene), which have high electrical conductivity and good mechanical strength, and can effectively isolate different layers of electrodes to avoid direct current contact.
[0086] Through the synergistic effect of this three-layer structure, the active metal electrode can achieve efficient and stable lithiation reaction during the pre-lithiation process, while ensuring safety and effective conduction of current.
[0087] In combination with the first aspect, in some embodiments of the present invention, the number of layers of the spiral curling structure can be multiple layers. If more materials need to be processed, the device can be made larger and have more layers.
[0088] The multilayer design of the spiral curled structure can provide a larger surface area. In this way, the contact area between the active metal electrode and the negative electrode material is increased, thereby improving the efficiency of the lithiation reaction. When processing more materials, increasing the number of layers helps to fully utilize the surface of the active metal electrode and promote faster lithiation reactions. The multilayer structure can better ensure that each layer of material can be evenly lithiated, avoiding the problem of uneven lithiation caused by excessive material accumulation. This helps to ensure the uniformity of the pre-lithiation reaction and improve the performance of the negative electrode material.
[0089] Furthermore, the multi-layer design of the spiral curling structure enables the device to process more negative electrode materials and meet the needs of large-scale industrial production. As the number of layers increases, the device can process more materials and meet the needs of high throughput in the production process. The number of spiral layers can be flexibly increased or decreased according to demand to meet the production requirements of different scales. This flexibility allows the device to be adjusted as the production scale expands, avoiding bottleneck problems caused by equipment limitations.
[0090] As the number of layers of the spiral structure increases, the temperature and humidity of each layer of the material can be more easily balanced during the reaction, avoiding local overheating or overcooling. This helps reduce the need for external heating or cooling systems, thereby improving energy efficiency and reducing energy consumption. The increase in the number of layers of the spiral curled structure means that the material can obtain lithium sources in a more efficient way during the lithiation reaction, thereby shortening the reaction time and further reducing the production cycle and energy consumption.
[0091] The multilayer structure also helps ensure that each layer of material can be uniformly pre-lithiated, avoiding the problem of some materials not being fully lithiated due to the single-layer structure. This makes the electrochemical performance of the treated negative electrode material more consistent. Through the multilayer design, the lithiation effect of each layer can be more finely controlled, avoiding local over-lithiation or under-lithiation, thereby improving the overall stability of the negative electrode material and the cycle life of the battery.
[0092] It can be understood that the spiral structure has better space utilization efficiency and can process more materials in a limited space. Compared with the traditional flat design, the spiral design can improve the processing capacity without changing the equipment volume. The multi-layer spiral structure makes the equipment design more compact and can integrate more processing units in the same volume, saving plant space and improving the overall layout efficiency of the production line.
[0093] It should also be noted that the number of layers of the spiral curled structure can be flexibly adjusted according to actual production needs and material properties. This flexibility allows the device to adapt to the pre-lithiation needs of a variety of negative electrode materials, including materials with different particle sizes, morphologies or chemical properties. The multi-layer structure of the device can be modularly designed, which allows the device to be easily expanded or reduced to adapt to production needs of different scales, and even to achieve rapid switching between small and large batch production.
[0094] The multi-layer spiral structure enables faster processing of each batch of materials, avoiding the layer-by-layer processing method in the traditional single-layer structure and improving the efficiency of batch production. As the number of layers increases, more materials can be processed per unit time, further optimizing the production process. As a result, the multi-layer design of the spiral curled structure provides higher efficiency, flexibility, processing capacity and quality control for the pre-lithiation device. As the number of layers increases, the device can not only improve the reaction efficiency, but also better meet the needs of large-scale production, while optimizing space utilization and saving energy consumption. Through sophisticated structural design, the equipment can maintain the quality consistency of the negative electrode material and the stability of the battery performance while increasing the processing volume, adapting to diverse production needs.
[0095] In combination with the first aspect, in some embodiments of the present invention, reference Figure 5 As shown, the reaction chamber 1000 includes a reaction chamber cylinder 1005, and a reaction chamber upper cover 1006 and a reaction chamber lower cover 1007 detachably connected to the reaction chamber cylinder 1005. The reaction chamber cylinder 1005, the reaction chamber upper cover 1006 and the reaction chamber lower cover 1007 are made of insulating material.
[0096] In combination with the first aspect, in some embodiments of the present invention, the reaction chamber cylinder 1005 and the reaction chamber upper cover 1006 are connected by fastening bolts, and a sealing rubber ring is provided between the reaction chamber cylinder and the reaction chamber upper cover.
[0097] In combination with the first aspect, in some embodiments of the present invention, a first electrode and a second electrode connected to the active metal electrode are provided in the reaction chamber, and a first through hole and a second through hole are provided on the upper cover of the reaction chamber, and the first electrode and the second electrode are respectively inserted into the interior of the reaction chamber through the first through hole and the second through hole.
[0098] In combination with the first aspect, in some embodiments of the present invention, the reaction chamber is further provided with a liquid injection port and a reaction chamber pressure gauge. The liquid injection port is used to inject electrolyte into the reaction chamber. The pressure gauge monitors the pressure in the chamber during the reaction.
[0099] In combination with the first aspect, in some embodiments of the present invention, the injection port is connected to an injection pump.
[0100] In combination with the first aspect, in some embodiments of the present invention, reference Figure 4As shown, the interior of the reaction chamber is divided into a negative electrode powder holding area 1013 and an active metal electrode area.
[0101] In combination with the first aspect, in some embodiments of the present invention, reference Figure 2 As shown, the drying bin 2000 includes a drying bin cylinder 2003, and a drying bin upper cover 2004 and a drying bin lower cover 2005 detachably connected to the drying bin cylinder 2003. The drying bin cylinder 2003, the drying bin upper cover 2004 and the drying bin lower cover 2005 are made of insulating materials.
[0102] In combination with the first aspect, in some embodiments of the present invention, the drying bin cylinder body 2003 and the drying bin upper cover 2004 are connected by fastening bolts 1008, and a sealing rubber ring is provided between the drying bin cylinder body 2003 and the drying bin upper cover 2004.
[0103] In combination with the first aspect, in some embodiments of the present invention, the heating device 2002 is a heating coil.
[0104] In combination with the first aspect, in some embodiments of the present invention, the drying chamber 2000 is further provided with a drying chamber pressure gauge 2008 , a liquid extraction pump interface 2006 , a vacuum pump interface 2007 and a thermometer 2009 .
[0105] In combination with the first aspect, in some embodiments of the present invention, the liquid pump interface is connected to a liquid pump.
[0106] In combination with the first aspect, in some embodiments of the present invention, the metal pre-activation device is connected to an external power source, and the external power source is connected to the first electrode and the second electrode.
[0107] In a second aspect, in some embodiments of the present invention, there is provided a method for preactivating metal of a negative electrode material using the metal preactivation device of the first aspect of the present invention, comprising the following steps:
[0108] S1: Add the negative electrode material to be treated into the reaction chamber, inject the electrolyte, and turn on the power to perform metal pre-activation treatment;
[0109] S2: Open the valve, the negative electrode material that has been pre-activated by the metal enters the drying chamber from the reaction chamber, the waste liquid flows through the filter and is removed, and the heating device is turned on to dry the negative electrode material to obtain the negative electrode material that has been pre-activated by the metal.
[0110] It should be noted that, taking pre-lithiation as an example, the negative electrode material metal pre-activation method of the present invention has at least the following beneficial effects:
[0111] It can improve the cycle stability of negative electrode materials. Through pre-lithiation treatment, the negative electrode material can react with lithium before being put into battery assembly to form a stable solid electrolyte interface (SEI) film. The formation of the SEI film can significantly improve the cycle stability of the negative electrode material and reduce the side reactions caused by direct contact between the electrolyte and the negative electrode material during the charge and discharge process.
[0112] It can improve the initial capacity of the battery. Pre-lithiation of the negative electrode material can reduce the consumption of lithium ions during the initial charge, thereby increasing the initial capacity of the battery. Pre-lithiation helps to "activate" the negative electrode material in advance, ensuring a more efficient charging process.
[0113] Reduced waste of lithium source. By first reacting lithium with the negative electrode material during the pre-lithiation process, waste of lithium source during charging after battery assembly is avoided, thereby improving the utilization efficiency of lithium. The process of the method of the present invention includes the steps of pre-lithiation, waste liquid removal and drying treatment, which can effectively remove residues in the electrolyte and ensure that the performance of the negative electrode material is not damaged during the drying process, thereby improving production efficiency and material utilization.
[0114] Improved safety. By controlling the reaction between the electrolyte and the negative electrode material during the pre-lithiation process, possible safety hazards can be eliminated during the production stage, reducing overheating or other electrochemical instability in the subsequent use of the battery.
[0115] The consistency of negative electrode materials is improved. The method of the present invention ensures that each batch of negative electrode materials can be uniformly processed by standardizing the pre-lithiation process, thereby improving the quality consistency of the negative electrode materials and ensuring the consistency and reliability of the battery.
[0116] Reduced complexity of post-processing. Since the pre-lithiation treatment can effectively remove excess electrolyte and impurities, and further process them in the subsequent drying process, it simplifies the subsequent material processing steps and improves the simplicity and controllability of the entire manufacturing process.
[0117] Therefore, the pre-lithiation method of the present invention can improve battery performance while reducing production costs, improving the efficiency and safety of the manufacturing process, and has significant industrial application value.
[0118] In conjunction with the second aspect, in some embodiments of the present invention, the "negative electrode material to be treated" refers to a negative electrode material that requires metal pre-activation, such as pre-lithiation.
[0119] In combination with the second aspect, in some embodiments of the present invention, the electrolyte salt in the electrolyte includes lithium salt, sodium salt, potassium salt, calcium salt, magnesium salt, such as at least one of lithium hexafluorophosphate, lithium bis(trifluoromethanesulfonyl)imide, lithium tetrafluoroborate, lithium trifluoromethanesulfonate, lithium difluorooxalatoborate, and lithium nitrate.
[0120] In combination with the second aspect, in some embodiments of the present invention, the solvent added to the electrolyte is at least one of ethylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, dioxolane, and ethylene glycol dimethyl ether.
[0121] In combination with the second aspect, in some embodiments of the present invention, the electrolyte solvent additive is at least one of vinylene carbonate, fluoroethylene carbonate, vinyl sulfate, and propylene sulfite.
[0122] Connect the first electrode column and the second electrode column to the designated electrode. The current and time are determined according to the nominal specific capacity, first-week coulomb and efficiency of the negative electrode material. Turn on the power supply to perform pre-lithiation. After the pre-lithiation is completed, open the valve and the vacuum pump connected to the liquid extraction port to allow the mixture to enter the drying chamber.
[0123] After the pre-lithiation negative electrode material powder is loaded into the drying chamber, the valve is closed and the filter screen will filter the material. Then, the vacuum pump is connected through the liquid extraction pump interface and started to extract the filtered waste liquid. The heating coil is started to adjust the temperature of the reaction chamber. The pressure of the drying chamber is adjusted by an external vacuum pump through the vacuum pump interface. The pressure gauge and thermometer display and feedback. The liquid and gas extracted by the vacuum pump are treated as waste liquid and exhaust gas.
[0124] In combination with the second aspect, in some embodiments of the present invention, the temperature of the drying process is 70°C to 90°C.
[0125] In combination with the second aspect, in some embodiments of the present invention, the temperature of the drying process is 80°C.
[0126] In combination with the second aspect, in some embodiments of the present invention, the drying time is 8 hours to 10 hours.
[0127] In combination with the second aspect, in some embodiments of the present invention, during the drying process, the pressure of the drying chamber is 1×10 -4 Pa~1×10 -2 Pa.
[0128] In combination with the second aspect, in some embodiments of the present invention, during the drying process, the pressure of the drying chamber is 1×10 -3 Pa.
[0129] In combination with the second aspect, taking pre-lithiation as an example, in some embodiments of the present invention, a method for pre-lithiation of a negative electrode material using the metal pre-activation device of the first aspect of the present invention comprises the following steps:
[0130] S1: Open the upper cover of the reaction chamber, add the raw material negative electrode material powder into the reaction chamber, close the upper cover of the reaction chamber and seal it, open the injection port to inject the electrolyte, connect the first electrode column and the second electrode column to the positive and negative electrodes of the power supply respectively, and obtain a mixture of the pre-lithiation negative electrode and the electrolyte after sufficient reaction;
[0131] S2: Open the valve of the reaction chamber and the vacuum pump connected to the liquid extraction port of the drying chamber to allow the mixture to enter the drying chamber. After the mixture enters the drying chamber, the lower layer of liquid is extracted through the external liquid extraction pump of the liquid extraction port to accelerate the filtration of the material by the filter. After the filtration is completed, the valve is closed, and the power supply of the heating coil is turned on to heat the mixture. Then, the pressure of the drying chamber is reduced through the vacuum pump interface. The temperature and pressure in the chamber are fed back in real time by the pressure gauge and thermometer. The extracted liquid needs to be treated as waste liquid, and the gas extracted by the vacuum pump needs to be treated as exhaust gas. After drying, open the drying chamber cover of the drying chamber to take out the finished product, which is the finished product of the pre-lithiation negative electrode material powder.
[0132] The device and method of the present invention are applicable to other secondary battery negative electrode materials besides lithium ion batteries, including sodium ion batteries, potassium ion batteries, calcium ion batteries, magnesium ion batteries, and mixed ion batteries, such as lithium-sodium mixed ion batteries, lithium-potassium mixed ion batteries, lithium-calcium mixed ion batteries, lithium-magnesium mixed ion batteries, sodium-potassium mixed ion batteries, sodium-calcium mixed ion batteries, sodium-magnesium mixed ion batteries, calcium-magnesium mixed ion batteries, etc.
[0133] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.
[0134] In the description of the present invention, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.
[0135] Unless otherwise specified, "room temperature" in the present invention means 25°C±5°C.
[0136] Unless otherwise specified, "about" in the present invention means that the allowable error is within ±2%.
[0137] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased commercially.
[0138] Example 1
[0139] Taking pre-lithiation as an example, the metal pre-activation device for negative electrode materials of the present invention is used to perform pre-lithiation treatment on graphite negative electrode materials. The specific process is:
[0140] Natural graphite powder is directly used as the reaction raw material. 100g of natural graphite powder is added. The first efficiency of the natural graphite negative electrode is about 84%. It enters the reaction chamber through the feed port; and the electrolyte is injected through the injection port.
[0141] In this embodiment, the specific dimensions of the reaction chamber are: the inner wall diameter of the reaction chamber is 200 mm, and the height is 400 mm. The inner wall diameter of the drying chamber is 200 mm, and the height is 300 mm. The reaction chamber and the drying chamber are made of polytetrafluoroethylene (PTFE).
[0142] The formula of the pre-lithiation electrolyte used is ethylene carbonate:ethyl methyl carbonate=3:7+5% (volume ratio) fluoroethylene carbonate, and the solute is 1 mol / L lithium hexafluorophosphate.
[0143] The negative electrode and the positive electrode of the external power supply are connected through the first electrode column and the second electrode column. The discharge time is 10 hours and the discharge current is 558 mA.
[0144] After the pre-lithiation is completed, the valve is opened, the pre-lithiation graphite is placed in the drying chamber, filtered through the filter screen, and the filtered electrolyte is pumped away by the pump connected to the pumping port. The valve is closed, and the chamber is pumped into a negative pressure by the vacuum pump, and the pressure is 1×10 -3 Pa, the temperature in the chamber is adjusted to 80 °C by a heating wire and maintained for 8 h, and the obtained material is pre-lithiated graphite.
[0145] The obtained material is subjected to EDS spectrum test, such as Figure 6 And as shown in Table 1.
[0146] Table 1
[0147] Element ordinal Element Symbols Element Name Atomic content Quality content 6 C carbon 91.45 87.42 9 F fluorine 4.99 7.54 8 O oxygen 3.14 4.00 15 P phosphorus 0.42 1.05
[0148] according to Figure 6 As can be seen from Table 1, a uniform solid electrolyte layer is formed on the graphite surface.
[0149] The obtained materials were also subjected to XRD analysis. Figure 7 As shown, Li-C peak appeared in XRD.
[0150] The obtained materials were mixed according to the ratio of active material: conductive agent: binder = 8:1:1 (mass ratio). The selected conductive material was conductive carbon black and the binder was polyvinylidene fluoride, both of which were battery-grade materials.
[0151] N-methylpyrrolidone was selected as the adhesive solvent, mixed evenly and coated on the negative electrode current collector copper foil. After drying, the pre-lithiated graphite electrode was obtained and assembled into a negative electrode half-cell to test the coulombic efficiency and gram capacity in the first week.
[0152] Figure 8 and Fig. 9 The first-week charge and discharge curves of original graphite and pre-lithiated graphite show that the coulombic efficiency in the first week increases from 84% to 98%.
[0153] The difference between Example 2-25 and Example 1 lies in the solvent system in the reaction chamber, the pre-lithiation current density and time, as shown in Table 2.
[0154] Table 2
[0155] Example Electrolyte formula in the reaction chamber Prelithiation current and time First effect 2 <![CDATA[1M LiPF 6 in EC:EMC=3:7+5%FEC]]> 0.558A 8h 96.1% 3 <![CDATA[1M LiPF 6 in EC:EMC=3:7+5%FEC]]> 0.558A 6h 93.6% 4 <![CDATA[1M LiPF 6 in EC:EMC=3:7+5%FEC]]> 0.558A 4h 90.8% 5 <![CDATA[1M LiPF 6 in EC:EMC=3:7+5%FEC]]> 0.558A 2h 87.9% 6 <![CDATA[1M LiPF 6 in EC:EMC=3:7+5%FEC]]> 1.116A 5h 95.7% 7 <![CDATA[1M LiPF 6 in EC:EMC=3:7+5%FEC]]> 1.116A 4h 93.1% 8 <![CDATA[1M LiPF 6 in EC:EMC=3:7+5%FEC]]> 1.116A 3h 90.8% 9 <![CDATA[1M LiPF 6 in EC:EMC=3:7+5%FEC]]> 1.116A 2h 88.5% 10 <![CDATA[1M LiPF 6 in EC:EMC=3:7+5%FEC]]> 1.116A 1h 86.4% 11 <![CDATA[1M LiPF 6 in EC:EMC=3:7]]> 0.558A 10h 93.7% 12 <![CDATA[1M LiPF 6 in EC:EMC=3:7]]> 0.558A 8h 91.8% 13 <![CDATA[1M LiPF 6 in EC:EMC=3:7]]> 0.558A 6h 89.6% 14 <![CDATA[1M LiPF 6 in EC:EMC=3:7]]> 0.558A 4h 87.7% 15 <![CDATA[1M LiPF 6 in EC:EMC=3:7]]> 0.558A 2h 85.9% 16 <![CDATA[1M LiPF 6 in EC:EMC=3:7]]> 1.116A 5h 92.5% 17 <![CDATA[1M LiPF 6 in EC:EMC=3:7]]> 1.116A 4h 90.8% 18 <![CDATA[1M LiPF 6 in EC:EMC=3:7]]> 1.116A 3h 88.9% 19 <![CDATA[1M LiPF 6 in EC:EMC=3:7]]> 1.116A 2h 88.4% 20 <![CDATA[1M LiPF 6 in EC:EMC=3:7]]> 1.116A 1h 86.2% 21 <![CDATA[1M LiTFSI in DOL+0.2M LiNO 3 ]]> 0.558A 10h 97.7% 22 <![CDATA[1M LiTFSI in DOL+0.2M LiNO 3 ]]> 0.558A 8h 95.8% 23 <![CDATA[1M LiTFSI in DOL+0.2M LiNO 3 ]]> 0.558A 6h 93.4% 24 <![CDATA[1M LiTFSI in DOL+0.2M LiNO 3 ]]> 0.558A 4h 90.4% 25 <![CDATA[1M LiTFSI in DOL+0.2M LiNO 3 ]]> 0.558A 2h 87.2%
[0156] It can be seen from Table 2 that with the changes in the electrolyte formula, pre-lithiation current and time in the reaction chamber in different embodiments, the results of the first effect (first charging efficiency) show a certain regularity.
[0157] LiPF 6 Performance in EC:EMC formulations:
[0158] When using LiPF 6 When EC:EMC=3:7 is used as the electrolyte formula, the first efficiency generally shows a downward trend with the increase of current density, the change of pre-lithiation current and time. For example, when the current is 0.558A, as the discharge time decreases, the first efficiency decreases from 96.1% to 85.9% (Examples 2 to 15).
[0159] Similarly, when the current increases to 1.116 A, as the discharge time decreases, the first efficiency also gradually decreases, from 95.7% to 86.2% (Example 6 to Example 20). This phenomenon shows that a longer discharge time and a lower current density can usually achieve a higher first efficiency.
[0160] Performance of LiTFSI in DOL formulation:
[0161] When using LiTFSI at DOL+0.2MLiNO 3When the formula is used, the first efficiency is generally high, especially at a longer discharge time. For example, in Example 21, when the discharge is performed at 0.558A for 10 hours, the first efficiency is as high as 97.7%, and even if the discharge time is shortened, the first efficiency remains at a high level. This shows that this electrolyte formula can provide better first efficiency than LiPF6 in EC:EMC formula.
[0162] Effect of current and discharge time on first effect:
[0163] Longer discharge time and lower current density help improve the first efficiency. In most embodiments, longer discharge time (such as 8h, 10h) and lower discharge current (such as 0.558A) usually achieve higher first efficiency. For example, the first efficiency in Example 1 (0.558A, 10h) is 94%, while the first efficiency of the embodiment with shorter time or higher current (such as Example 10, 1.116A, 1h) is only 86.4%.
[0164] This indicates that lower current density and longer discharge time help to pre-lithiate the graphite anode material more fully, thereby improving the first efficiency.
[0165] Shorter time and higher current density usually lead to a decrease in the first efficiency. Relatively speaking, an increase in current density and a shortened discharge time will lead to incomplete lithiation of the graphite material during the pre-lithiation process, thus affecting the first efficiency. For example, the first efficiency of Example 6 (1.116A, 5h) is 95.7%, but the first efficiency of Example 10 (1.116A, 1h) is only 86.4%. This change shows that although increasing the current density can speed up the reaction process, it may also lead to uneven and insufficient lithiation.
[0166] Comparison of different formulations: Using LiTFSI in DOL+0.2MLiNO 3 The first efficiency is generally higher when the formula is used. Even at a shorter discharge time (such as 2 hours), the first efficiency can still be maintained at a high level (87.2%). This shows that the LiTFSI system is superior to the LiPF 6 The system has better reaction efficiency or is more suitable for the pre-lithiation of graphite anode.
[0167] In contrast, when LiPF6 is used in the EC:EMC formulation, the initial efficiency decreases significantly as time decreases.
[0168] In summary, it can be seen from Table 1 that longer time and lower current density are beneficial to improving the first efficiency of graphite, but will increase production time. Although higher current and shorter time can improve production efficiency, they may lead to a decrease in the first efficiency. The choice of electrolyte formula also has a significant impact on the improvement of the first efficiency. The LiTFSI system performs better than the LiPF6 system, especially in short-term discharge.
[0169] From the data in Table 1, it can be seen that the discharge current, discharge time and electrolyte formula all have an important influence on the pre-lithiation effect of the negative electrode material. In order to obtain a higher first efficiency, a lower current density and a longer discharge time are more ideal, and choosing a suitable electrolyte formula (such as LiTFSI in DOL) can also significantly improve the first efficiency. In industrial applications, the production process can be optimized according to these rules to balance production efficiency and product quality.
[0170] Examples 26-55, other negative electrode materials for lithium batteries, the solvent system is the same as that of Example 1, the differences are the pre-lithiation current density, time and negative electrode materials: such as artificial graphite, mesophase carbon microbeads (MCMB), hard carbon, as shown in Table 3.
[0171] Table 3
[0172] Example Anode Materials Prelithiation current and time First effect 26 Artificial graphite 0.558A 10h 98.6% 27 Artificial graphite 0.558A 8h 96.8% 28 Artificial graphite 0.558A 6h 95.1% 29 Artificial graphite 0.558A 4h 93.4% 30 Artificial graphite 0.558A 2h 91.6% 31 Artificial graphite 1.116A 5h 96.3% 32 Artificial graphite 1.116A 4h 95.0% 33 Artificial graphite 1.116A 3h 93.7% 34 Artificial graphite 1.116A 2h 92.5% 35 Artificial graphite 1.116A 1h 91.3% 36 Mesocarbon Microspheres 0.558A 10h 96.9% 37 Mesocarbon Microspheres 0.558A 8h 95.3% 38 Mesocarbon Microspheres 0.558A 6h 93.6% 39 Mesocarbon Microspheres 0.558A 4h 91.7% 40 Mesocarbon Microspheres 0.558A 2h 90.1% 41 Mesocarbon Microspheres 1.116A 5h 96.4% 42 Mesocarbon Microspheres 1.116A 4h 94.8% 43 Mesocarbon Microspheres 1.116A 3h 93.2% 44 Mesocarbon Microspheres 1.116A 2h 91.4% 45 Mesocarbon Microspheres 1.116A 1h 89.7% 46 Hard Carbon 0.558A 10h 82.2% 47 Hard Carbon 0.558A 8h 79.8% 48 Hard Carbon 0.558A 6h 77.5% 49 Hard Carbon 0.558A 4h 75.1% 50 Hard Carbon 0.558A 2h 72.7% 51 Hard Carbon 1.116A 5h 81.2% 52 Hard Carbon 1.116A 4h 79.0% 53 Hard Carbon 1.116A 3h 76.9% 54 Hard Carbon 1.116A 2h 74.7% 55 Hard Carbon 1.116A 1h 72.5%
[0173] From Table 3 we can see that:
[0174] 1. Effect of pre-lithiation current and time on the first effect:
[0175] Artificial graphite: With the increase of pre-lithiation current density and time, the first efficiency gradually decreases. For example, the first efficiency at 0.558A10h is 98.6%, while at 1.116A1h the first efficiency drops to 91.3%.
[0176] Mesocarbon microbeads (MCMB): There is a similar trend. With the increase of pre-lithiation current density and time, the first efficiency gradually decreases. For example, the first efficiency at 0.558A10h is 96.9%, while at 1.116A1h the first efficiency drops to 89.7%.
[0177] Hard carbon: The first efficiency of hard carbon is generally low, and with the increase of pre-lithiation current and time, the first efficiency decreases significantly. For example, the first efficiency at 0.558A10h is 82.2%, while at 1.116A1h the first efficiency drops to 72.5%.
[0178] 2. Differences in initial efficiency of different negative electrode materials:
[0179] The first efficiency of artificial graphite and mesophase carbon microspheres is significantly higher than that of hard carbon. In artificial graphite and mesophase carbon microspheres, the first efficiency is basically above 90%, while the first efficiency of hard carbon is generally less than 80%.
[0180] Under the same pre-lithiation conditions (eg 0.558A10h), the first efficiencies of artificial graphite and mesophase carbon microspheres are 98.6% and 96.9%, respectively, while that of hard carbon is 82.2%.
[0181] 3. Relationship between pre-lithiation time and current density:
[0182] For artificial graphite and mesophase carbon microspheres, longer prelithiation time (e.g., 10 h) and lower current density (e.g., 0.558 A) can achieve higher first efficiency, indicating that milder prelithiation conditions may help to improve the first efficiency.
[0183] In contrast, for hard carbon, the first efficiency is always low regardless of the prelithiation current and time, indicating the poor initial electrochemical performance of hard carbon.
[0184] Therefore, the current density and time of pre-lithiation have a significant impact on the first efficiency of different negative electrode materials. Longer time and lower current pre-lithiation conditions usually achieve higher first efficiency.
[0185] Compared with hard carbon, artificial graphite and mesophase carbon microbeads perform better in the pre-lithiation process, especially artificial graphite, which has the best performance and higher initial efficiency.
[0186] The first efficiency of hard carbon is relatively low. No matter how the pre-lithiation current and time change, its first efficiency always fails to reach the level of other materials, indicating that its initial performance as a negative electrode material is poor.
[0187] Example 56
[0188] The pre-lithiation device for negative electrode materials of the present invention is used to perform pre-lithiation treatment on graphite negative electrode materials. The specific process is as follows:
[0189] According to the scheme of the present invention, taking the alloyed negative electrode material silicon negative electrode material of lithium battery as an example, nano silicon powder is directly used as the reaction raw material, and 200g of nano silicon powder is added according to the size of the warehouse, and the first effect of the unmodified silicon negative electrode is about 62.4%, and it enters the reaction warehouse through the feed port; the electrolyte is injected through the injection port, and the formula of the pre-lithiation electrolyte used is ethylene carbonate: ethyl methyl carbonate = 3:7 + 5% fluoroethylene carbonate, and the solute is 1 mol / L lithium hexafluorophosphate;
[0190] The negative and positive electrodes of the external power supply are connected through the first electrode column and the second electrode column. According to the specific capacity of the silicon material, the discharge time is set to 50h and the discharge current is 1.0A. After the pre-lithiation is completed, the valve is opened, the pre-lithiation graphite is placed in the drying chamber, filtered through the filter screen, and the filtered electrolyte is pumped away by the pump connected to the liquid extraction port. The valve is closed, and the chamber is pumped into a negative pressure by a vacuum pump, and the pressure is 1×10 -3Pa, adjust the temperature in the chamber to 80°C through the heating wire and maintain it for 8h. The obtained material is pre-lithiated nano-silicon. The obtained materials are mixed according to the ratio of active material: conductive agent: adhesive = 8:1:1. The selected conductive material is conductive carbon black and the adhesive is polyvinylidene fluoride, both of which are battery-grade materials. Select N-methylpyrrolidone as the adhesive solvent, mix well and apply it on the negative electrode current collector copper foil. After drying, the pre-lithiated silicon pole piece is obtained, and the negative electrode half-battery is assembled to test the first week coulomb efficiency and gram capacity. The first week coulomb efficiency is increased from 66.4% to 79.7%.
[0191] Examples 57-70, other negative electrode materials for lithium batteries, the solvent system is the same as that of Example 1, the differences are the pre-lithiation current density, time and negative electrode materials, alloyed negative electrode materials such as silicon, tin, aluminum, as shown in Table 4.
[0192] Table 4
[0193] Example Anode Materials Prelithiation current and time First effect 57 silicon 1.0A 40h 77.1% 58 silicon 1.0A 30h 74.4% 59 silicon 1.0A 20h 71.7% 60 silicon 1.0A 10h 69.6% 61 tin 1.116A 10h 85.6% 62 tin 1.116A 8h 83.1% 63 tin 1.116A 6h 80.9% 64 tin 1.116A 4h 78.6% 65 tin 1.116A 2h 76.4% 66 aluminum 1.116A 10h 83.0% 67 aluminum 1.116A 8h 80.2% 68 aluminum 1.116A 6h 77.8% 69 aluminum 1.116A 4h 75.6% 70 aluminum 1.116A 2h 73.2%
[0194] From Table 4 we can see that:
[0195] 1. Differences in initial efficiency of different negative electrode materials:
[0196] The initial efficiency of silicon is significantly lower than that of tin and aluminum. For example, the initial efficiency of silicon at 1.0A for 40 hours is 77.1%, while the initial efficiencies of tin and aluminum at 1.116A for 10 hours are 85.6% and 83.0%, respectively. This shows that the initial electrochemical performance of silicon is poor and the initial efficiency after pre-lithiation is low.
[0197] The first effects of tin and aluminum are generally high, especially tin, which is always higher than silicon, and still maintains a good first effect (76.4% 85.6%) in a short time (such as 2 hours). The performance of aluminum is close to that of tin, although slightly lower, but also better than silicon.
[0198] 2. Effect of pre-lithiation current and time on the first effect:
[0199] For silicon, the first efficiency gradually decreases as the pre-lithiation time shortens. For example, the first efficiency at 1.0A for 40 hours is 77.1%, while it drops to 69.6% at 1.0A for 10 hours. This shows that a longer pre-lithiation time helps to improve the first efficiency for silicon, but even for a longer time, the first efficiency of silicon is still lower than that of tin and aluminum.
[0200] For tin and aluminum, the first efficiency also decreases as the pre-lithiation time shortens, but the decrease is smaller. For example, tin decreases from 85.6% at 1.116A10 hours to 76.4% at 1.116A2 hours, and aluminum decreases from 83.0% to 73.2%. This shows that tin and aluminum can still maintain a high first efficiency under short-time pre-lithiation, which is better than silicon.
[0201] 3. Differences in the effects of changes in pre-lithiation current and time on different materials:
[0202] For silicon, a longer pre-lithiation time (such as 40 hours) can significantly improve the first efficiency, but even with a longer pre-lithiation time, the first efficiency of silicon is still lower than that of tin and aluminum, indicating that silicon is prone to expansion, volume change and decreased conductivity during the lithiation process, resulting in a lower first efficiency.
[0203] The initial effects of tin and aluminum are relatively stable, and the variation range of different pre-lithiation times is small, especially for tin, indicating that they are more stable during the lithiation process and can maintain a higher initial effect.
[0204] Silicon shows a lower first efficiency in Table 4, and its first efficiency gradually decreases as the pre-lithiation time shortens. Silicon negative electrode materials may encounter more volume expansion and other problems during the pre-lithiation process, which affects their first efficiency.
[0205] The first effects of tin and aluminum are generally high, and as the pre-lithiation time shortens, the first effect decreases less. Tin can still maintain a good first effect in a short period of time, showing good stability.
[0206] Tin and aluminum are more suitable negative electrode materials than silicon, especially under pre-lithiation conditions, they can provide higher first efficiency and show better performance and stability.
[0207] For other negative electrode materials of lithium batteries in Examples 71 to 85, the solvent system is the same as that in Example 1, the differences are the pre-lithiation current density, time and negative electrode materials, and the composite negative electrode materials of carbon materials and alloying materials, such as silicon-carbon negative electrode, aluminum-carbon negative electrode, and tin-carbon negative electrode, as can be seen in Table 5.
[0208] Table 5
[0209]
[0210]
[0211] From Table 5 we can see that:
[0212] 1. Differences in initial efficiency of different negative electrode materials:
[0213] The initial efficiency of silicon carbon is generally higher, and its overall performance is better than that of aluminum carbon and tin carbon. For example, the initial efficiency of silicon carbon of 1.116A10 hours is 97.1%, which is significantly higher than 96.3% of aluminum carbon and 93.2% of tin carbon.
[0214] The first efficiency of silicon carbon gradually decreases with the reduction of pre-lithiation time, but even under 2 hours of pre-lithiation conditions, its first efficiency is still 84.7%, which is much higher than that of tin carbon and aluminum carbon.
[0215] The initial efficiencies of aluminum carbon and tin carbon are relatively low, especially the initial efficiency of tin carbon, which remains above 85% (85.4%) under a relatively short time (2 hours) of pre-lithiation. However, compared with silicon carbon, the initial efficiencies of tin carbon and aluminum carbon gradually decrease faster.
[0216] 2. Effect of pre-lithiation current and time on the first effect:
[0217] The initial efficiency of silicon carbon and aluminum carbon gradually decreases with the shortening of pre-lithiation time, but remains at a high level. For example, silicon carbon decreases from 97.1% at 1.116A10 hours to 84.7% at 2 hours, and aluminum carbon decreases from 96.3% at 1.116A10 hours to 84.3% at 2 hours.
[0218] The first effect of tin carbon decreased less, from 93.2% of 1.116A10 hours to 85.4% of 2 hours, showing a relatively more stable performance.
[0219] 3. Differences in stability of different materials:
[0220] The initial effect of silicon-carbon remains at a high level even at a shorter pre-lithiation time, which indicates that the silicon-carbon composite material may alleviate the expansion problem of the silicon negative electrode in some way (such as the synergistic effect of carbon), making its performance more stable during the pre-lithiation process.
[0221] The first efficiency of aluminum carbon and tin carbon is slightly lower than that of silicon carbon, and the first efficiency decreases greatly during short-time pre-lithiation, but the overall performance is still acceptable. The first efficiency of aluminum carbon and tin carbon is relatively stable, but compared with silicon carbon, it still shows a certain gap.
[0222] 4. Effect of material optimization:
[0223] The advantage of silicon-carbon materials lies in their high initial efficiency and their ability to maintain good electrochemical properties for a short period of time. This may be because the performance of silicon is optimized through compounding with carbon, which reduces the volume expansion problem and improves the initial efficiency.
[0224] As composite materials, aluminum carbon and tin carbon perform relatively well, but fail to reach the level of silicon carbon. Especially in a short period of pre-lithiation, the initial efficiency of tin carbon and aluminum carbon decreases rapidly, showing the limitations of their performance.
[0225] The first efficiency of silicon-carbon composite materials is better than that of aluminum-carbon and tin-carbon as a whole, and they still maintain a high first efficiency under short-time pre-lithiation, indicating that silicon-carbon composite materials have good electrochemical stability.
[0226] Aluminum carbon and tin carbon have lower initial efficiencies, and as the pre-lithiation time shortens, the initial efficiencies decrease more significantly, showing relatively poor stability, although their performance is still higher than that of silicon materials.
[0227] Silicon-carbon materials show strong adaptability and good initial electrochemical performance, and are suitable for high-efficiency negative electrode material applications.
[0228] The present invention has been described in detail above in conjunction with the embodiments, but the present invention is not limited to the above embodiments, and various changes can be made within the knowledge scope of ordinary technicians in the relevant technical field without departing from the purpose of the present invention.
Claims
1. A device for preactivating negative electrode material metal, characterized in that: It includes a reaction chamber and a drying chamber arranged vertically, wherein a pipeline is connected between the reaction chamber and the drying chamber, a valve is arranged on the pipeline, an active metal electrode is arranged in the reaction chamber, a filter screen and a heating device are arranged in the drying chamber, and the drying chamber is also connected to an exhaust gas treatment system and a waste liquid treatment system.
2. The device according to claim 1, characterized in that The active metal electrode comprises an active material layer, a copper current collector layer and a separator layer which are arranged in sequence.
3. The device according to claim 1, characterized in that The active metal electrode is a spirally coiled structure.
4. The device according to claim 1, characterized in that The reaction chamber comprises a reaction chamber cylinder, and a reaction chamber upper cover and a reaction chamber lower cover detachably connected to the reaction chamber cylinder. The reaction chamber cylinder, the reaction chamber upper cover and the reaction chamber lower cover are made of insulating material.
5. The device according to claim 4, characterized in that The reaction chamber is provided with a first electrode and a second electrode connected to the active metal electrode, the reaction chamber upper cover is provided with a first through hole and a second through hole, and the first electrode and the second electrode are respectively inserted into the interior of the reaction chamber through the first through hole and the second through hole.
6. The device according to claim 1, characterized in that The reaction chamber is also provided with a liquid injection port and a reaction chamber pressure gauge.
7. A method for preactivating negative electrode material metal using the device according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1: adding the negative electrode material to be treated into the reaction chamber, injecting the electrolyte, and turning on the power supply to perform metal pre-activation treatment; S2: Open the valve, the negative electrode material that has been pre-activated by metal enters the drying chamber from the reaction chamber, the waste liquid flows through the filter and is removed, and the heating device is turned on to dry the negative electrode material to obtain the negative electrode material that has been pre-activated by metal.
8. The method according to claim 7, characterized in that The drying treatment temperature is 70° C. to 90° C.; and / or the drying treatment time is 8 h to 10 h.
9. The method according to claim 7, characterized in that: During the drying process, the pressure of the drying chamber is 10 -2 Pa~10 -4 Pa.
10. A secondary battery negative electrode material, characterized in that: The method is obtained by preactivation using the device according to any one of claims 1 to 6 or the method according to any one of claims 7 to 9.
Citation Information
Patent Citations
Anode pre-lithiation for high energy li-ion battery
CN114026712A
Integrated battery cell pre-lithiation device and method
CN116053607A
Pre-lithiation method and application of lithium ion battery
CN116722239A
Integrated cell pre-lithiation device
CN219321383U
Pre-lithiation method and device for negative pole pieces of lithium-ion battery
CN105845894A